Literacy learning and teaching : language as social practice in the primary school (South Melbourne : Macmillan Education, 1993)
This book is about: The social construction of literacy in the primary school; Children's literature; Beginning reading with children's literature; Managing the language program; The language of social issues; ...
Keywords: English language; Literacy; Language arts; Children's literature; Literacy; Language arts (Primary).; English language -- Study and teaching (Primary); Children's literature -- Study and teaching (Primary)